2018
DOI: 10.1177/0143034318773523
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mindfulness-based colouring for test anxiety in adolescents

Abstract: The purpose of this study was to compare the effectiveness of a mindfulness art activity (mandala) with a free draw/colouring activity on test anxiety in adolescents with an examination of gender differences, and to assess the effect of dispositional mindfulness on students' experience of mindfulness and test anxiety states. Participants were 193 Grade 8 students (56.6% female; M age ¼ 13.49 years, SD ¼ 0.50) randomly assigned to a mandala (n ¼ 97) or free draw/colouring condition (n ¼ 96). Students completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 65 publications
(123 reference statements)
4
22
0
Order By: Relevance
“…As such, coloring a structured mandala was more effective at reducing math anxiety than doodling on a white sheet of paper with a mean decrease of 0.45. This finding is consistent with previous analytical findings supporting the theoretical assumption that coloring a structured mandala is an effective mindfulness approach to reduce university students' anxiety in comparison to doodling (control condition) (Curry & Kasser, 2005;van der Vennet & Serice, 2012;Carsley & Heath, 2018). However, in the study no significant differences were found in math anxiety levels when comparing the pre-drawn (structured) group and the coloring of the mandala group, t (102) = -.062, p = .47.…”
Section: Resultssupporting
confidence: 91%
“…As such, coloring a structured mandala was more effective at reducing math anxiety than doodling on a white sheet of paper with a mean decrease of 0.45. This finding is consistent with previous analytical findings supporting the theoretical assumption that coloring a structured mandala is an effective mindfulness approach to reduce university students' anxiety in comparison to doodling (control condition) (Curry & Kasser, 2005;van der Vennet & Serice, 2012;Carsley & Heath, 2018). However, in the study no significant differences were found in math anxiety levels when comparing the pre-drawn (structured) group and the coloring of the mandala group, t (102) = -.062, p = .47.…”
Section: Resultssupporting
confidence: 91%
“…In contrast to self-compassion, we did not observe any changes in our measures of mindfulness and mentalization following the intervention. Although very brief mindfulness-based interventions have been shown to have positive effects in adolescents (113,114), our intervention may not have been long enough to produce measurable changes (as reflected by changes in scores on the selected self-report measure) in these skills, which may require a period of training longer than four weeks, particularly in college students who typically have numerous competing demands. Unlike in conventional mindfulness interventions (e.g., mindfulness based cognitive therapy, which is comprised of 8 twohour sessions with daily practice), participants in this program were not required to engage in extensive exercises between sessions (the mindfulness exercises were recommended only) because we felt that such a requirement would reduce retention levels and overall feasibility of the intervention; our initial piloting suggested that the students were unlikely to complete such assigned "homework".…”
Section: Changes In Symptoms and Resilience-promoting Capacities Follmentioning
confidence: 99%
“…Most forms of informal mindfulness, generally described as an additional activity in which one applies a mindful attention, such as in yoga, have yielded measurable benefits in stress reduction, mental health, and other health conditions, including reduced pain perception (Carsley & Heath, 2018;Hardison & Roll, 2016;Strauss et al, 2014). Informal mindfulness is defined by the application of mindful awareness while experiencing participation in everyday activities without perseveration on competing thoughts, feelings, and body sensations (Kabat-Zinn, 2003).…”
Section: History Of Mindfulness In Occupational Therapymentioning
confidence: 99%
“…Seven articles were initially identified that closely matched the review question and search criteria. Two were published in the psychology literature and described Level 1 studies in which the benefit of stress reduction through embedding mindfulness into either a coloring activity with adolescents (Carsley & Heath, 2018) or washing dishes with undergraduate students (Hanley et al, 2015) was found to be of benefit in measured outcomes. The authors in both studies suggested that applying informal mindfulness in the context of a meaningful activity was worth pursuing for preventive stress management.…”
Section: Summary Of the Review Findingsmentioning
confidence: 99%